Law Enforcement, Criminal Provisions, and Administrative Sanctions in the Indonesian Legal System - Adinda Apriliany; Diki Zukriadi (Sean Institute, 2026)
Law enforcement is the process of realizing the values of justice, certainty, and benefit in the life of the nation and state. In the context of the Indonesian legal system, law enforcement is not solely oriented towards the imposition of criminal sanctions, but also involves administrative legal instruments that are preventive and corrective in nature. Criminal provisions are used to punish violations that have a serious level of wrongdoing and social impact, while administrative sanctions are used to enforce compliance without going through lengthy criminal court proceedings. This article analyzes the relationship, differences, and application of criminal and administrative sanctions in the Indonesian legal system, as well as examining how these two instruments play a role in achieving effective law enforcement. The research method used is normative juridical with a regulatory approach and legal doctrine analysis. The results show that the effectiveness of law enforcement in Indonesia is highly dependent on the balance between repressive (enforcement) and preventive (prevention) efforts, as well as coordination between legal institutions that apply the principles of substantive and procedural justice.